ANALISIS POTENSI FRAUD PENGGUNAAN DANA DESA KEPADA MASYARAKAT TERDAMPAK COVID-19 DI DESA SE-KECAMATAN TEMPURSARI KABUPATEN LUMAJANG - Selva Fersa Sonia; Dwiyani Sudaryanti; Siti Aminah Anwar (Universitas Islam Malang, 2022)
This study aims to analyze the potential for fraud in the use of village funds to communities affected by Covid-19 in villages throughout the Tempursari District, Lumajang Regency. This research was conducted by distributing questionnaires to village officials at the Village Office in Tempursari District, Lumajang Regency. The method used in this research is descriptive research with a quantitative approach. The population in this study was 56 village officials, and the sample used was 52 people. The data analysis technique used in this study is SPSS Statistics for Windows 25. The results of this study reveal that individual morality (X1) affects the potential for fraud in the use of village funds for communities affected by Covid-19 (Y). Law enforcement (X2) affects the potential for fraud in the use of village funds for communities affected by Covid-19 (Y). Organizational Culture (X3) has no effect on the potential for fraud in the use of village funds for communities affected by Covid-19 (Y). The competence of the apparatus (X4) affects the potential for fraud in the use of village funds for communities affected by Covid-19 (Y).Keywords: Fraud Potential, Individual Morality, Law Enforcement, Organizational Culture, Apparatus Competence